Prevalence and factors associated with hyperphosphatemia in continuous ambulatory peritoneal dialysis patients: A cross-sectional study - Yin, Xiaojing; Zhang, Fan; Shi, Yan (Frontiers in Medicine, 2023)
Objective: To investigate the prevalence and factors of hyperphosphatemia among continuous ambulatory peritoneal dialysis patients in a tertiary public hospital in Shanghai, China. Methods: The single-center cross-sectional study recruited end-stage renal failure who received continuous ambulatory peritoneal dialysis (CAPD) for at least three months. The participants aged 18 to 80 had undergone CAPD between July 1, 2021, and May 30, 2022, in Shanghai, China. The patients' sociodemographic, clinical, and laboratory data were collected prospectively from medical records and via face-to-face interviews. A sample size of convenience decides the sample size. This study used the Information-Motivation-Behavioral skills Model (IMB) as a theoretical framework. The questionnaire included Knowledge and behavior of diet and medication in patients with hyperphosphatemia of chronic kidney disease, Self-efficacy for managing chronic disease, and Social support rating scale. Univariate analysis and binary logistic regression were performed to identify the influencing factors of hyperphosphatemia by SPPS 27.0. Results: One hundred and forty-one CAPD patients (73% hyperphosphatemia) were included in the final analysis. In logistic regression analysis, dialysis vintage (OR: 0.975, 95%CI: 0.957-0.993), dialysis exchanges (OR: 0.317, 95%CI: 0.131-0.768), urine output(OR:0.997, 95%CI: 0.995-0.999), serum albumin (OR:1.166, 95%CI:1.008-1.349), serum creatinine(OR:1.005, 95%CI: 1.001-1.008), hyperphosphatemia knowledge behavior score (OR:0.888, 95%CI: 0.797-0.991), social support level (OR:0.841, 95%CI:0.765-0.925) were the influencing factors of hyperphosphatemia. Conclusions: Hyperphosphatemia is a frequent complication in CAPD patients. Dialysis vintage, dialysis exchanges, urine output, serum albumin, serum creatinine, hyperphosphatemia knowledge behavior, and social support were the associated factors of hyperphosphatemia in CAPD patients. It is crucial for healthcare to provide exceptional care of phosphorus management strategies to keep phosphorus balance among CAPD patients.